Peninjauan Kembali dipersimpangan putusan MK No. 34 Tahun 2014 dan SEMA No. 7 Tahun 2014 - Mursyidi, Mursyidi (Syura: Journal of Law, 2024)
This study explores the legal controversy related to the submission of PK in Indonesia with a focus on the Constitutional Court Decision No. 34 of 2014 and SEMA No. 7 of 2014. The 1945 Constitution provides a legal basis that must be obeyed by all people and state organs. The Constitutional Court and the Supreme Court have different but interrelated authorities in maintaining justice and legal certainty. The Constitutional Court Decision contained in No. 34 of 2014 allows PK more than once, contrary to Article 268 of the Criminal Procedure Code which allows PK only once. The Supreme Court responded to the decision by issuing SEMA No. 7 of 2014 which limits PK to only being submitted once, except in special conditions. The method used in this study is normative juridical, with secondary data as the main source. Data analysis was carried out qualitatively with a descriptive and prescriptive approach based on historical and comparative analysis. The results of the study indicate that the Constitutional Court Decision No. 3 of 2013 emphasizes the aspects of justice and human rights, providing the opportunity for multiple PKs with the condition of novum. However, SEMA No. 7 of 2014 was issued to maintain legal certainty by limiting PK to only one time. This study highlights the importance of the balance between justice and legal certainty in the Indonesian justice system